PENGEMBANGAN MEDIA BIGBOOK UNTUK ANAK USIA DINI DI TK MUSLIMAT NU 254 NURUL ISHLAH - Riyadlotus Sholichah; Roudlotul Badi'ah (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2022)
This study aims to: 1) Develop Bigbook media for early childhood aged 4-5 years, 2) Find out the response of students to the use of Bigbook learning media for early childhood aged 4-5 years. This research uses research methods Research and Development (R&D), with development procedures from ADDIE (Analysis – Design – Develop – Implement – Evaluate). The subjects in this study were children of group A1 of TK Muslimat NU 254 Nurul Ishlah. With the data collection instrument used in the form of questionnaires given to material experts, media experts and educators to test bigbook learning feasibility media for early childhood and student response questionnaires to see student responses to learning media developed by researchers. The results of this study are: 1) Producing products in the form of Bigbook learning media, the feasibility of the products that have been developed is feasible with a percentage of 74.6% based on the assessment of media experts, 93.3% by material experts in the category of decent snagat and educators with an overall percentage is 83.95% in the very decent category. 2) the response of the children of group A1 of TK Muslimat NU 254 Nurul Ishlah and the class teacher to the use of Bigboook learning media, namely 85.71% and 90% were included in the eligibility criteria